Analysis of 3516 B Engine Damage on a 793 C Truck Based on Oil Using Laboratory Test Schedule Oil Sampling (SOS) Wear Data with Failure Mode Effect Analysis Method (FMEA) - Nazha Ali Christy; Hadi Pranoto; Irgi Ahmad Faturrahman (Institute for Research on Innovation and Industrial System (IRIS), 2022)
Engine failure is difficult to predict, especially related to the age of engine components. Analysis of engine failure can be done based on the oil seen from the trend of wear rates, predicting the possibility of components that are damaged in the engine. The method used is a combination of oil analysis in order to determine the component that is damaged and determine the age of the component based on the trend of the element value with the Component Meter Unit (CMU) and implement the Failure Mode and Effect Analysis ( FMEA) method to support the analysis by looking at the value of the Risk Priority Number (RPN). The result of this analysis is that there is slightly above normal wear on the Cu and Pb elements, where in the last sample the values for Cu 3 and Pb 5 are Particle Per Meter (PPM). CMU predictions are also generated before passing the threshold of the wear limit based on the value of each element. Fe at 17931 hours, Cu at 25963 hours, Pb at 14417 hours and Al at 16927 hours. Wear is indicated from the FMEA analysis, there are 3 with the highest RPN, namely cutting filter result with RPN 280, noise with RPN 175 and scratch with RPN 160. From these Cu and Pb elements it can be determined which components are the source of damage, namely rocker arm bushings, wrist pin bushings, governor drive and bushings, timing gear thrust bearings, turbocharger bearings, camshaft lifter roller pins, air compressor bearings, rear cluster gear bearings and main and rod bearings. From this research, new research data can be developed, namely if there are additional parameters such as oil viscosity value.